Innovating evidence procedure in international construction arbitration - Jones, Doug (2020)
The complexity of construction disputes commands special attention and constant innovation. Fortunately, arbitration is well-equipped to meet the challenges of such disputes, due to its flexibility and adaptability. This paper discusses three areas of innovation in evidence procedure unique to construction disputes: institutional, technological and procedural. Due consideration is also given to the virtual hearing, an innovation which has proven critical to the survival of arbitration amidst the COVID-19 pandemic. Technology, while valuable, will not improve the efficiency of arbitration alone: it must be used in conjunction with procedural innovations. The implementation of procedural, technological and institutional advancements by a proactive tribunal and open-minded parties can create boundless innovation and provide maximum value for all involved.